Analysis of Internal Control System in Cash Receipt at PT Angkasa Migasindo Batu Raja - Yulita Eka Fitri (Lembaga Riset dan Inovasi Al-Matani, 2023)
Cash is one of the assets that has an important role in the development of the company. Cash important because it is the most liquid assets (liquid). In an effort to protect cash from theft and misuse, the company must have an internal control system over cash from the time it is received until it is deposited in the bank. PT Angkasa Migasindo Baturaja is a company engaged in the field of LPG gas. In carrying out its operational activities there are always transactions cash. Therefore, the company needs an internal control procedure for cash receipts. This study aims to determine the effectiveness of internal control of cash receipts at PT Angkasa Migasindo Baturaja. The research method uses analytical methods descriptive. The test results show that the cash receipts internal control system has been effective, contrary to the internal control of cash disbursements. While the expenditure internal control system cash is not yet effective, because there are still elements of internal control within the company that have not fully carried out, including the placement of cashiers in the same room as other employees, cash in hand and the cashier is not insured, bank reconciliation is not done by the inspection internal audit, and the check stamp held by the check maker, which should be by the accounting department for control.